Oral nutritional supplement helps to improve nutritional status of dialysis dependent patients: a systematic review and meta-analysis of randomized controlled trials - Ren, Song; Yao, Xiaoxiu; Ren, Shangqing; Feng, Yunlin (Frontiers in Nutrition, 2023)
Background The prevention and treatment of malnutrition holds remarkable implications in the overall management of dialysis patients. However, there remains a dearth of comprehensive evaluations regarding the impact of oral nutrition supplement (ONS) on all pertinent dimensions of malnutrition in the dialysis population. Methods A systematic search was conducted in MEDLINE, EMBASE, and Cochrane Central Library. RCTs that had assessed the effects of oral nutritional supplement in dialysis-dependent populations were considered eligible. Outcomes included laboratory indicators, anthropometric measures, nutritional indices, dialysis adequacy, body composition analysis measures, and systemic inflammation indicators. The risk of bias was assessed according to Cochrane guidelines. Weighted mean difference (WMD) or standardized mean difference (SMD) with 95% confidence intervals (CIs) were pooled using a random-effects model. Results In all, 22 RCTs with 1,281 patients were included. The pooled analyses revealed the serum ALB, BMI, nPCR, and MIS improved by 1.44 g/L (95% CI: 0.76, 2.57), 0.35 kg/m2 (95% CI: 0.17, 0.52), 0.07 g/(kg d) (95% CI, 0.05, 0.10), and −2.75 (95% CI, −3.95, −1.54), respectively following ONS treatments when compared to control treatments. However, no significant differences were observed in relation to the other outcomes examined. 15 studies were rated as having high risk of bias. Visual inspection of the funnel plot and Egger test argued against the presence of publication bias. Conclusion ONS treatments helps to improve the nutritional status of dialysis dependent patients. More evidence is needed from future investigations with longer study duration and standardized procedures to support long-term use of ONS in this population. Systematic review registration https://www.crd.york.ac.uk/prospero/, Identifier CRD 42023441987.